The Effects of Antisense miRNA-20a Alone or in Combination with Imatinib on K562 Cell Proliferation - Zhou, Ying; He, Dongmei; Zeng, Jinrong; Bao, Shijie; Lai, Jing; Weng, Yujun; Chen, Shengting (Frontiers in Pharmacology, 2017)
Objective: The effects of microRNA-20a (miR-20a) antisense oligonucleotides (ASODNs) on the proliferation and apoptosis of K562 cells were investigated, and the effects of these ASODNs in combination with imatinib on K562 cells were preliminarily observed. Methods: miR-20a ASODNs and scrambled oligonucleotides (SODNs) were chemically synthesized, and the later was used as the control. miR-20a ASODNs were transfected into K562 cells using Lipofectamine 2000 transfection reagent, and the expression of miR-20a was detected using real-time quantitative RT-PCR (qRT-PCR). The CCK8 assay was performed to detect the inhibition of the cell growth rate. The cells were stained by Hoechst 33258 to detect apoptotic cell morphology. Annexin V/PI double staining was used to detect the cell apoptosis rate using flow cytometry. The protein expression levels of E2F1, P21, and Bim in the K562 cell line were detected using western blotting. Results: The qRT-PCR results showed that the expression level of miR-20a in K562 cells transfected with miR-20a ASODNs was lower than those in the normal control, SODN and blank transfection groups (p < 0.05). miR-20a ASODNs significantly inhibited the growth of K562 cells as compared to the controls (p < 0.05). The Hoechst staining results showed morphological changes, suggesting apoptosis. The cell apoptosis rates in the ASODN group was (13.9 ± 1.5)%, which was significantly higher than that in the normal control group (1.84 ± 0.21)%, blank transfection group (3.21 ± 0.32)%, and SODN group (3.72 ± 0.44)% (p < 0.05). The protein expression of E2F1 and P21 in K562 cells transfected with miR-20a ASODNs were higher, while the level of Bim protein was significantly lower than that in the control groups. When miR-20a ASODNs were combined with imatinib, the growth of K562 cells was significantly inhibited as compared to the ASODN treatment alone, imatinib alone, and SODN+imatinib groups (p < 0.05). Conclusions: miR-20a ASODNs could induce apoptosis and inhibit the proliferation of K562 cells. In addition, imatinib combined with miR-20a ASODNs can increase the inhibitory effect on K562 cell proliferation.